Cell surface immunoglobulin. XX. Antibody responsiveness of subpopulations of B lymphocytes bearing different isotypes (The Rockefeller University Press, 1977)
Murine spleen cells were depleted of specific B-cell subpopulations bearing different immunoglobulin isotypes by means of complement- mediated cytolysis after treatment with antisera specific for micron- and gamma-chains. The functional effect of this depletion was measured by assaying both the primary and secondary plaque-forming cell responses of the residual cells after transfer to carrier-primed lethally irradiated hosts. The results suggest that cells bearing IgM are the progenitors of plaque-forming cells in the primary response and cells bearing IgG are the major progenitors of IgG plaque-forming cells in the secondary response. The quantity of IgM on progenitors of secondary IgM plaque-forming cells decreases markedly as the interval between primary immunization and antigenic challenge increases. Long- term memory cells for the secondary IgM response bear small amounts of both IgM and IgG.